Corporate Governance, Bank Specific Characteristics, Banking Industry Characteristics, and Intellectual Capital (IC) Performance of Banks in Arab Gulf Cooperation Council (GCC) Countries - Mahfoudh Abdul Karem Al-Musalli; Ku Nor Izah Ku Ismail (Asian Academy of Management Journal of Accounting and Finance, 2012)
This paper examines the level of intellectual capital (IC) performance of listed banks in Arab Gulf Cooperation Council (GCC) countries using VAIC methodology and investigates the hypothesized impact of several corporate governance variables, bank specific characteristics and banking industry characteristics on IC performance. We extend previous research on determinants of IC performance by considering domestic and foreign strategic institutional ownership, bank specific characteristics and banking industry characteristics. Our findings show that board size, number of independent directors, family ownership and domestic strategic institutional ownership have significant relationship with IC performance. In addition, our study provides evidence that except for bank internationality, bank specific characteristics and banking industry characteristics play important roles in determining IC performance among GCC banks.